2016
DOI: 10.1111/jvim.13890
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Evaluation of Angiogenesis in the Large Airways of Horses with Heaves Using Narrow Band Imaging

Abstract: BackgroundHeaves is a severe debilitating condition of horses, characterized by lower airway inflammation and permanent structural changes of the bronchial wall. Chronic inflammation promotes the formation of new vessels, a phenomenon known as angiogenesis. Narrow band imaging (NBI) endoscopy is a noninvasive technique that enhances the visualization of submucosal vessels, and commonly is employed for the study of angiogenesis in human patients.ObjectivesUsing NBI, we aimed to determine whether or not the cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…In this study, we utilized a histomorphometric software program (Visiopharm, Horsholm, Denmark) to quantitatively evaluate immunohistochemical stain densities in a semi-automated, unbiased manner [31,32]. This histomorphometric algorithm-based analysis has also been used to quantify degree of angiogenesis in equine large airways [33], however a common approach for wound healing assessment in the equine involves a semi-subjective scoring system [3,28,29]. One study of human patients diagnosed with breast cancer found that the histomorphometric software program outperformed traditional pathologist-based analysis of prognostic histologic biomarkers [34].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we utilized a histomorphometric software program (Visiopharm, Horsholm, Denmark) to quantitatively evaluate immunohistochemical stain densities in a semi-automated, unbiased manner [31,32]. This histomorphometric algorithm-based analysis has also been used to quantify degree of angiogenesis in equine large airways [33], however a common approach for wound healing assessment in the equine involves a semi-subjective scoring system [3,28,29]. One study of human patients diagnosed with breast cancer found that the histomorphometric software program outperformed traditional pathologist-based analysis of prognostic histologic biomarkers [34].…”
Section: Discussionmentioning
confidence: 99%
“… 18 Although several studies have identified the presence of angiogenesis in humans with asthma, 19 , 20 , 21 , 22 with an increased number of subepithelial vessels and vascular area in lung tissue, 11 , 23 literature on lung angiogenesis in asthmatic horses is scarce. A 2012 study 24 showed an increased vascular density of superficial tracheal vessels in asthmatic horses, when evaluated by narrow‐band imaging. However, no differences were observed at the level of the bronchi, conflicting with results obtained in humans.…”
Section: Introductionmentioning
confidence: 99%